PDGFR‐β Plays a Key Role in the Ectopic Migration of Neuroblasts in Cerebral Stroke. (4th October 2015) - Sato, Hikari; Ishii, Yoko; Yamamoto, Seiji; Azuma, Erika; Takahashi, Yoriko; Hamashima, Takeru; Umezawa, Akihiro; Mori, Hisashi; Kuroda, Satoshi; Endo, Shunro; Sasahara, Masakiyo
Abstract: The neuroprotective agents and induction of endogenous neurogenesis remain to be the urgent issues to be established for the care of cerebral stroke. Platelet‐derived growth factor receptor beta (PDGFR‐β) is mainly expressed in neural stem/progenitor cells (NSPCs), neurons and vascular pericytes of the brain; however, the role in pathological neurogenesis remains elusive. To this end, we examined the role of PDGFR‐β in the migration and proliferation of NSPCs after stroke. A transient middle cerebral‐arterial occlusion (MCAO) was introduced into the mice with conditional Pdgfrb ‐gene inactivation, including N‐PRβ‐KO mice where the Pdgfrb‐ gene was mostly inactivated in the brain except that in vascular pericytes, and E‐PRβ‐KO mice with tamoxifen‐induced systemic Pdgfrb ‐gene inactivation. The migration of the DCX + neuroblasts from the subventricular zone toward the ischemic core was highly increased in N‐PRβ‐KO, but not in E‐PRβ‐KO as compared to Pdgfrb ‐gene preserving control mice. We showed that CXCL12, a potent chemoattractant for CXCR4‐expressing NSPCs, was upregulated in the ischemic lesion of N‐PRβ‐KO mice. Furthermore, integrin α3 intrinsically expressed in NSPCs that critically mediates extracellular matrix‐dependent migration, was upregulated in N‐PRβ‐KO after MCAO. NSPCs isolated from N‐PRβ‐KO rapidly migrated on the surface coated with collagen type IV or fibronectin that are abundant in vascular niche and ischemic core. PDGFR‐β was suggested to be critically involved in pathological neurogenesis through the regulation of lesion‐derived chemoattractant as well as intrinsic signal of NSPCs, and we believe that a coordinated regulation of these molecular events may be able to improve neurogenesis in injured brain for further functional recovery. Stem Cells 2016;34:685–698